Influence of Attentional Focus Instructions on Motor Performance Among Adolescents With Severe Visual Impairment. Issue 6 (December 2019) - McNamara, Scott W. T.; Becker, Kevin A.; Weigel, William; Marcy, Peter; Haegele, Justin
Substantial research has demonstrated that an external (vs. internal) attentional focus enhances motor performance among various populations. Interest has recently grown in examining the effects of attentional focus among individuals with visual impairments (VI), and, to date, research results have been conflicting with some studies supporting a potential benefit to an external focus among adults with VI, while a study of children with severe VI was inconclusive regarding this benefit. The present investigation compared the effects of an internal versus an external attentional focus on a discrete throwing task among adolescents with severe VI. We recruited 13 participants with a visual acuity score of less than 6/60 and had them throw a Goalball (25 cm ball with bells often used in competitive sports designed for people with VI) as fast as possible for three familiarization trials, three internal focus trials, and three external focus trials. These participants threw the ball with significantly higher velocity when using an external focus than in other conditions, indicating a benefit from an external focus for this population when performing this discrete task.